2013
DOI: 10.1523/jneurosci.2385-13.2013
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic Mechanisms Underlying Strong Reciprocal Connectivity between the Medial Prefrontal Cortex and Basolateral Amygdala

Abstract: The medial prefrontal cortex (mPFC) plays a critical role in the control of cognition and emotion. Reciprocal circuits between the mPFC and basolateral amygdala (BLA) are particularly important for emotional control. However, the neurons and synapses that link these brain regions remain largely unknown. Here we examine long-range connections between the mouse mPFC and BLA, using whole-cell recordings, optogenetics, and two-photon microscopy. We first identify two non-overlapping populations of layer 2 pyramida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
158
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 146 publications
(178 citation statements)
references
References 58 publications
18
158
2
Order By: Relevance
“…In targeted recordings from labeled neurons, we measured both AMPA-R EPSCs at −70 mV and NMDA-R EPSCs at +40 mV. By comparing the EPSC amplitude ratios at pairs of cells, we were able to control for variability in viral injections and expression between slices and animals (Little and Carter, 2013; MacAskill et al, 2014; McGarry and Carter, 2016). We found that both AMPA-R and NMDA-R EPSCs are much larger at AC neurons than AS neurons (AS/AC ratio: AMPA-R = 0.29, 95% CI = 0.14–0.61, p = 0.004; NMDA-R = 0.38, 95% CI = 0.2–0.74, p = 0.008; n = 9 pairs, 7 animals) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In targeted recordings from labeled neurons, we measured both AMPA-R EPSCs at −70 mV and NMDA-R EPSCs at +40 mV. By comparing the EPSC amplitude ratios at pairs of cells, we were able to control for variability in viral injections and expression between slices and animals (Little and Carter, 2013; MacAskill et al, 2014; McGarry and Carter, 2016). We found that both AMPA-R and NMDA-R EPSCs are much larger at AC neurons than AS neurons (AS/AC ratio: AMPA-R = 0.29, 95% CI = 0.14–0.61, p = 0.004; NMDA-R = 0.38, 95% CI = 0.2–0.74, p = 0.008; n = 9 pairs, 7 animals) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…3A). The resulting input-specific quantal EPSCs (qEPSCs) provide a direct measure of unitary synaptic strength (amplitude) and an indirect indication of number of connections and presynaptic properties (frequency) (Goda and Stevens, 1994; Little and Carter, 2013; MacAskill et al, 2014). In the absence of stimulation, baseline miniature EPSC (mEPSC) frequency was similar at AC, AS and AH neurons in medial BLA (AS = 2.0 ± 0.3 Hz, n = 8 cells; AC = 1.7 ± 0.2 Hz, n = 15 cells; AH = 1.8 ± 0.3 Hz, n =7 cells; p = 0.2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A possible stress-sensitive input to basal dendrites comes from anterograde tracing that demonstrates a major monosynaptic input projecting from the basolateral amygdala nucleus (BLA) to the basal dendrites of mPFC layer V cells (Bacon et al, 1996;Gabbott et al, 2012). Also, a direct BLA input to layer II pyramidal cells has been shown by anterograde optogenetic methods (Little and Carter, 2013). The main cortically projecting excitatory neurons of the BLA are glutaminergic pyramidal cells.…”
Section: Introductionmentioning
confidence: 99%